A rabies virus-vectored vaccine expressing two copies of the Marburg virus glycoprotein gene induced neutralizing antibodies against Marburg virus in humanized mice. Issue 1 (31st December 2023) - Bi, Jinhao; Wang, Haojie; Han, Qiuxue; Pei, Hongyan; Wang, Hualei; Jin, Hongli; Jin, Song; Chi, Hang; Yang, Songtao; Zhao, Yongkun; Yan, Feihu; Ge, Liangpeng; et al.
ABSTRACT: Marburg virus disease (MVD) is a lethal viral haemorrhagic fever caused by Marburg virus (MARV) with a case fatality rate as high as 88%. There is currently no vaccine or antiviral therapy approved for MVD. Due to high variation among MARV isolates, vaccines developed against one strain fail to protect against other strains. Here we report that three recombinant rabies virus (RABV) vector vaccines encoding two copies of GPs covering both MARV lineages induced pseudovirus neutralizing antibodies in BALB/c mice. Furthermore, high-affinity human neutralizing antibodies were isolated from a humanized mouse model. The three vaccines produced a Th1-biased serological response similar to that of human patients. Adequate sequential immunization enhanced the production of neutralizing antibodies. Virtual docking suggested that neutralizing antibodies induced by the Angola strain seemed to be able to hydrogen bond to the receptor-binding site (RBS) in the GP of the Ravn strain through hypervariable regions 2 (CDR2) and CDR3 of the VH region. These findings demonstrate that three inactivated vaccines are promising candidates against different strains of MARV, and a novel fully humanized neutralizing antibody against MARV was isolated.